2020
DOI: 10.1016/j.celrep.2020.107956
|View full text |Cite
|
Sign up to set email alerts
|

Active Lysogeny in Listeria Monocytogenes Is a Bacteria-Phage Adaptive Response in the Mammalian Environment

Abstract: Summary Some Listeria monocytogenes ( Lm ) strains harbor a prophage within the comK gene, which renders it inactive. During Lm infection of macrophage cells, the prophage turns into a molecular switch, promoting comK gene expression and therefore Lm intracellular growth. During this process, the prophage does not produce infective phages or cause bacterial lysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…Putative antirepressor and transcriptional regulator in bacteriophage HCF1 genome indicates the presence of a mechanism for decrease in the transcription of early genes and increase in the transcription of late genes. Recently, it has been established that late gene activation promotes the lytic pathway and the early gene activation plays a role in active lysogeny ( Pasechnek et al, 2020 ). In addition, no ORFs were identified corresponding to excisionase, integrase, or repressor genes in the genome of HCF1.…”
Section: Resultsmentioning
confidence: 99%
“…Putative antirepressor and transcriptional regulator in bacteriophage HCF1 genome indicates the presence of a mechanism for decrease in the transcription of early genes and increase in the transcription of late genes. Recently, it has been established that late gene activation promotes the lytic pathway and the early gene activation plays a role in active lysogeny ( Pasechnek et al, 2020 ). In addition, no ORFs were identified corresponding to excisionase, integrase, or repressor genes in the genome of HCF1.…”
Section: Resultsmentioning
confidence: 99%
“…The principle of the method and the high observed efficiency gives a better understanding of prophage–host interactions. The prophage-excision event mostly attributed to the phage disadvantage for staying integrated [ 37 ] or regulated by the host for a temporary extra-chromosomal state (active lysogeny) [ 38 ], but here, we showed that under certain conditions, when the prophage’s contents endanger the host, it would prefer to lose the whole prophage rather than the specific risk-containing region. This fact emphasizes the need for curing rather than deletion methods for such regions.…”
Section: Discussionmentioning
confidence: 63%
“…Prophages inserted into comK and tRNA genes were assigned to genera of Siphoviridae that are known to only infect Listeria . Surprisingly, in the isolate HC189, a 67 Kb Myovirus was inserted into comK , a site usually occupied by Siphoviridae (Pasechnek et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence that prophages can mediate beneficial phenotypes for their host. Phages mediate resistance or virulence properties in numerous bacterial species (Harrison & Brockhurst, 2017), and in Listeria , Siphoviruses inserted into comK were found to regulate the gene in a symbiotic manner (Pasechnek et al 2020). Here, we discovered phage-mediated carriage of cadmium resistance and various antimicrobials in Listeria , suggesting that prophages contribute to the spread of phenotypes supporting persistence.…”
Section: Discussionmentioning
confidence: 99%